CHALLENGES IN ENGLISH MATERIALS EVALUATION: LOCALLY, NATIONALLY, AND GLOBALLY - Okky Leo Agusta (Universitas Indo Global Mandiri, 2022)
Language teaching materials are very substantial in language teaching and learning process. Therefore, teacher of English should be thoroughly in choosing English materials before the materials used in classroom. This study aims to portray challenges in English materials evaluation. Library research in qualitative used in this study in elaborating challenges in English Material evaluation: Locally, Nationally (Indonesia), and Globally. This research involves a collection of some textbooks, journals, articles, virtual resources and internet access.One of the criteria in local context for language learning must include the target culture and local culture. The debate in using English material has never been whether to prioritize the target culture or local culture. In national context, the challenge that must be faced by teachers is to create a blue line that is in line between the material taught in the classroom and government policies in education or commonly known as the curriculum. Globally, the biggest challenge in evaluating English material is the ability of the evaluators themselves to make decisions. There are many considerations that must be taken into account in taking judgment on an English material. All efforts in evaluating English material are to optimize English learning outcomes for students